The Distribution And Abundance Of Small Apes In The Greater Taman Negara Pahang Landscape - Mohd Rameli, Nurul Iza Adrina (2021)
Two species of small apes, or gibbons, inhabit Taman Negara Pahang, Hylobates lar and Symphalangus syndactylus, and both are listed as Endangered in the IUCN Red List. However, the current distribution and abundance of small apes in Malaysia are not well known. This study had four main goals: 1) to assess the habitat characteristics of small ape habitat using on ground vegetation data and satellite imagery data inside and outside of Taman Negara, 2) to estimate the group density of H. lar and S. syndactylus inside and outside the park boundaries, 3) to determine whether there is a relationship between the densities of two the sympatric small ape species Taman Negara, 4) to evaluate the effect of habitat ecology on small ape density. To achieve the study goals, two general methods were used: 1) vegetation “speed” plots were established in small ape listening areas and habitat variables were recorded, i.e., the number of trees, tree diameter at breast height (DBH), tree height, percentage of canopy cover, and tree species; 2) active acoustic surveys were conducted in listening areas by recording the small ape calls from three listening posts (LP)s placed ca. 300-500 m from each other located inside and outside of Taman Negara Pahang. Data from each set of LPs were recorded for three consecutive days from 7 am to 11 am, and the listeners recorded: 1) direction of the small ape calls from listeners in each LPs, 2) duration of the calls, and 3) estimated distance of the call from listeners